(untitled) (Belmont, CA, 2011)
Designed for beginning teachers, Classroom teaching skills, 9th edition, introduces the teacher as "reflective decision maker," responsible for planning, implementing, evaluating, and making management decisions in the classroom. Each chapter considers a particular teaching skill, first discussing the theory behind it, and then presenting the reader with practice situations in which knowledge about the skill can be applied and evaluated. The Ninth Edition continues to address the importance of core INTASC standards, and highlights developing issues including the "Digital Divide," the use of personal digital assistants (PDAs) in and outside of the classroom, cooperative learning, and dealing with behavioral issues.
Giáo dục học
Keywords: Classroom management,Educational technology,Quản lý lớp học,Giáo dục kỹ thuật